Blood-based prognostic biomarkers in Crohn's Disease patients on biologics: a promising tool to predict endoscopic outcomes. (3rd August 2021) - Crispino, Federica; Grova, Mauro; Maida, Marcello; Renna, Sara; Mocciaro, Filippo; Casà, Angelo; Rizzuto, Giulia; Tesè, Lorenzo; Scimeca, Daniela; Di Mitri, Roberto; Macaluso, Fabio Salvatore; Orlando, Ambrogio
ABSTRACT: Objective: There is a growing need for biomarkers to predict therapeutic outcome in Crohn's disease (CD). Main outcome measures: The aim was to evaluate whether NLR (neutrophil-to-lymphocyte ratio), PLR (platelet-to-lymphocyte ratio), ELR (eosinophil-to-lymphocyte ratio), and ENLR (eosinophil*neutrophil-to-lymphocyte ratio), could be prognostic biomarkers of endoscopic response (ER) when starting biologics. Research design and methods: Patients with CD who started biologics were enrolled. Multivariate analysis was used to evaluate whether NLR, PLR, ELR and ENLR at baseline and at w12 could predict ER (Simple Endoscopic Score for Crohn's disease [SES-CD] ≤2 or SES-CD≤2 and Rutgeerts i0-i1) after 52 weeks of treatment. Area under the curve (AUC) was calculated to find the cutoffs. Results: 107 patients were included. Patients who achieved ER had significantly lower baseline NLR (p = 0.025), ELR (p = 0.013), and ENLR (p = 0.020) compared with those without ER; results after 12 weeks of treatment for ELR (p = 0.006) and ENLR (p = 0.003). AUC was 0.64 (p = 0.003), 0.67 (p = 0.006) and 0.65 (p = 0.014) for NLR, ELR and ENLR. Conclusions: Low NLR, ELR and ENLR can predict ER and could be used in clinical practice for a better management of CD patients.